Amantadine has potential for the treatment of COVID-19 because it inhibits known and novel ion channels encoded by SARS-CoV-2 - Trine Lisberg Toft-Bertelsen (Nature Portfolio, 2021)
Toft-Bertelsen et al. describe repurposing of anti-influenza drug amantadine and its derivatives for the treatment of SARS-CoV-2. They show that Amantadine, Emodin and Xanthene show significant blockage of ionchannels formed by SARS-CoV-2 which are crucial for its assembly and pathophysiology.